Plant Cyclophilins: Multifaceted Proteins With Versatile Roles - Singh, Harpreet; Kaur, Kirandeep; Singh, Mangaljeet; Kaur, Gundeep; Singh, Prabhjeet (Frontiers in Plant Science, 2020)
Cyclophilins constitute a family of ubiquitous proteins that bind cyclosporin A (CsA), an immunosuppressant drug. Several of these proteins possess peptidyl-prolyl cis-trans isomerase (PPIase) activity that catalyzes the cis-trans isomerization of the peptide bond preceding a proline residue, essential for correct folding of the proteins. Compared to prokaryotes and other eukaryotes studied until now, the cyclophilin gene families in plants exhibit considerable expansion. With few exceptions, the role of the majority of these proteins in plants is still a matter of conjecture. However, recent studies suggest that cyclophilins are highly versatile proteins with multiple functionalities, and regulate a plethora of growth and development processes in plants, ranging from hormone signaling to the stress response. The present review discusses the implications of cyclophilins in different facets of cellular processes, particularly in the context of plants, and provides a glimpse into the molecular mechanisms by which these proteins fine-tune the diverse physiological pathways.